Effect of home-based physical activity on older adults’ well-being in COVID-19 pandemic - Adeel Khoja; Naureen Ali (Türk Spor ve Egzersiz Dergisi)
COVID-19 pandemic has altered the life of older people that caused a significant impact on their daily routine. Subsequently this isolation leads to decrease physical activity and increase sedentary behaviour which has several consequences on older adults’ life. Though older adults need to remain at home because they are more likely to contract COVID-19, on the other hand, there is a need to avoid sedentary lifestyle and engage in physical activity. Many older adults. The pandemic has drastically effect the older adults physical activity. Despite that, many older adults continue to engage in physical activity within their confined home spaces. This reflects that pandemic has broadened the horizon of utilizing home spaces to promote physical activity and decrease sedentary behaviour.